2019
DOI: 10.1039/c9na00169g
|View full text |Cite
|
Sign up to set email alerts
|

MOF-templated cobalt nanoparticles embedded in nitrogen-doped porous carbon: a bifunctional electrocatalyst for overall water splitting

Abstract: A carboxylate based 3D-anionic MOF-derived bifunctional electrocatalyst was fabricated for overall water splitting through a one-pot carbonization technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 70 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…Recently, we reported the formation of a nanocomposite from a three-dimensional porous Co-MOF ( Co-AOIA ) . The presence of an anthracene moiety and DMF as a N-source in Co-AOIA helped in the formation of a Co nanoparticle embedded N-doped porous carbon ( Co@NPC1 ) upon carbonization.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the formation of a nanocomposite from a three-dimensional porous Co-MOF ( Co-AOIA ) . The presence of an anthracene moiety and DMF as a N-source in Co-AOIA helped in the formation of a Co nanoparticle embedded N-doped porous carbon ( Co@NPC1 ) upon carbonization.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that it may have been reduced by carbon or by the N 2 gas atmosphere, which subsequently evaporated at elevated temperatures and the remaining are further removed by acid leaching . The XRD spectra of Nb/Co–N–C and Mo/Co–N–C were similar to Co–N–C with a hump at 44°, indicating the presence of carbon (100) in the samples, but the Nb/Co–N–C sample also exhibited a small peak of the cobalt (111) plane according to the JCPDS card 15-0806 . The Bi/Co–N–C sample had one noticeable Bi peak of the (012) plane at 27° (JCPDS card 41-1246), indicating that metallic bismuth NPs were also present in the sample, which were confirmed by elemental mapping and XPS.…”
Section: Resultsmentioning
confidence: 99%
“…To develop such a catalyst, Zhang et al 44 synthesized MOF‐derived cobalt nanoparticles on N‐doped carbon (C‐MOF‐C2) catalyst for effective catalysis of OER. The produced catalyst showed a small onset potential of 1.50 V and reached the current density of 10 mA/cm 2 with 1.58 V. In another study, Nath et al 62 synthesized MOF‐templated Co nanoparticles inserted in N‐doped porous carbon (Co@NPC) for an OER electrocatalyst. A synergistic effect of Co nanoparticles and the N‐doped carbon makes Co@NPC electroactive towards OER with remarkable performance, stability, and durability.…”
Section: Monometallic Mofs As An Oer Electrocatalyst Precursormentioning
confidence: 99%